Self-knowledge and self-deception. - Young, H (Department of Economics (University of Oxford), 2008)
A person is concerned about self‐image if his utility function depends, not only on his actions, but also on his beliefs about what sort of person he is. This dual motivation problem makes it difficult, and in some cases impossible, for someone to learn who he really is based solely on his revealed behavior. Indeed, there are very simple situations, involving just two actions and two possible identities, such that, if there is any initial uncertainty about one’s true identity, it will never be resolved even when one has an infinite number of opportunities to act.